ANALISIS PENDAPATAN USAHATANI KETELA POHON DI KELURAHAN SIALANG RAMPAI KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Rizka Febri Ramadhani; Eliza Eliza; Shorea Khaswarina (Indonesian Journal of Agricultural Economics, 2020)
The purpose of this study was to (1) analyze production cost, income, efficiency and feasibillity of cassava farming, (2) identify problem in conducting cassava farming. The method used in this research is survey method with technique of sample selection by Random Sampling method. The number of respondents is 25 respondents. The results showed that the characteristics of farmer aged 30-56 years old with formal education to senior high school, the most experience for 11-15 years, almost all respondents have the number of dependents of families as many as 1-2 people and no toddlers, the land area ranges from 0.5 -1 Ha, and more than 50% of respondents have main occupations as farmers. The efficiency of cassava farming is 1,65 and the feasibille of cassava farming is 65,54%. It means cassava farming is worth to be develop.